2013
DOI: 10.1080/03670244.2013.768122
|View full text |Cite
|
Sign up to set email alerts
|

Wild Foods from Farm and Forest in the East Usambara Mountains, Tanzania

Abstract: This study explored the role of wild foods in the diets of children and mothers in the East

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 42 publications
4
81
0
2
Order By: Relevance
“…The findings in the present study corroborate the previous findings in DR Congo (12) , Benin (53) , Tanzania (57) , Ethiopia (69) and Cameroon (70) that indicated a wide gap between the number of traditionally known and the number of commonly consumed forest foods. The focus group respondents in the present study revealed a list of forty-seven forest plant foods, of which only seventeen were observed to be consumed during the 7 d recall period in the study.…”
Section: Knowledge Of Forest Foodssupporting
confidence: 92%
“…The findings in the present study corroborate the previous findings in DR Congo (12) , Benin (53) , Tanzania (57) , Ethiopia (69) and Cameroon (70) that indicated a wide gap between the number of traditionally known and the number of commonly consumed forest foods. The focus group respondents in the present study revealed a list of forty-seven forest plant foods, of which only seventeen were observed to be consumed during the 7 d recall period in the study.…”
Section: Knowledge Of Forest Foodssupporting
confidence: 92%
“…A mushroom locally known as “Kusaghizi” has a long tradition of being used as food by local communities in the Usambara mountains as first reported by Powell et al (2013). In a study by Juma et al (2016), which assessed antioxidant activities of saprobic mushrooms from Tanzania, “Kusaghizi” was included, but neither the study by Powell et al nor that of Juma et al reported a scientific name for “Kusaghizi”.…”
Section: Introductionmentioning
confidence: 99%
“…Only a handful of studies have been conducted that directly quantify the consumption of forest foods Rowland et al 2015). These studies originate from case studies of single communities in different locations, ecological, social and cultural contexts, use different methodologies and have mixed results (Blaney et al 2009;Golden et al 2011;Termote et al 2012;Powell et al 2013).…”
Section: Introductionmentioning
confidence: 99%